Dynamic voltage‐sharing among series‐connected IGBTs during turning‐on process. Issue 12 (1st June 2019) - Zhu, Jianxin; Xing, Yan; Ding, Shun; Hu, Haibing
Abstract : An active clamping circuit for voltage sharing among series‐connected insulated gate bipolar translators (IGBTs) during turning‐on process is proposed at first, which detects the C–E voltage of the leading IGBT and generates gate pumping current to slow down the turning‐on speed, and thus reduces the voltage difference between the IGBTs. Then, a turn‐on edge regulation algorithm for the driving signal is proposed, which further reduces the voltage spike and turn‐on power loss, and optimises the regulation speed. A time detection circuit is introduced to detect the pulse signal indicating the working time of the active clamping circuit for driving signal regulation. The turn‐on edge regulation for each IGBT is determined by the feature that the rising edge of the detected pulse signal coincides with the corresponding IGBT turn‐on edge delay. The experimental results prove the feasibility and effectiveness of the proposed method.